Pengaruh Efikasi Diri, Pelatihan Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Divisi Frontliner di PT BPR Indra Candra Singaraja - Ni Made Widnyani; Kadek Kristina Dewi (ARTHA SATYA DHARMA, 2022)
Improvement of employee creativity is based on the fact that creativity contributes to innovation, effectiveness, and survival of an organization. Creativity is needed in every government organization, including the LPD's internal supervisory organization, specifically Lembaga Pemberdayaan Lembaga Perkreditan Desa (LPLPD). The purpose of this study was to analyze the influence of leadership empowerment, intrinsic motivation, and workload on the employee creativity in LPLPD Bali. This study uses a quantitative approach with data collection techniques of questionnaires and documentation. The analytical techniques aremultiple linear regression analysis, coefficient of determination, F test, and t test. The results showed that 57.3% of employee creativity in LPLPD Bali’s variation was influenced by empowerment leadership, intrinsic motivation, and workload. Partial influence testing shows that there is a significant positive effect of theempowerment leadership and intrinsic motivation on employee creativity, while there is a significant negative effect of the workload on employee creativity. The leaders of LPLPD Bali are expected to implement an effective empowerment leadership style in influencing employee behavior, encouraging employees to feel motivated at work, along with evaluating the provision of appropriate workloads so that employees cancome up with creative ideas at work.